THE INFLUENCE OF TAXPAYER AWARENESS, TAX SOCIALIZATION, AND E-FILING IMPLEMENTATION ON INDIVIDUAL TAXPAYER COMPLIANCE WITH TAX SANCTIONS AS MODERATION ON TAXPAYERS REGISTERED AT THE PRATAMA TAX SERVICE OFFICE IN BEKASI - Lembah Dewi Andini; Sofia Maulida; Diva Ainiatun Nahlah (PT. Radja Intercontinental Publishing, 2026)
This study focuses on the level of taxpayer compliance. It aims to obtain empirical evidence on the influence of taxpayer awareness, tax socialization, and E-filing on taxpayer compliance with tax sanctions, with E-filing as a moderating variable. This study uses a quantitative research design. This research was conducted using a questionnaire distributed to all taxpayers in Bekasi City; 180 questionnaires were distributed via WhatsApp. Each questionnaire distributed contains 22 items for taxpayers to answer. To obtain the results of this study, the researcher used PLS-SEM version 3.0. This study found that taxpayer awareness and the implementation of E-filing had a positive and significant effect on taxpayer compliance, whereas tax socialization had a positive but nonsignificant effect. Tax sanctions are unable to moderate the influence of taxpayer awareness and tax socialization on taxpayer compliance, whereas they can moderate the effect of E-filing implementation on taxpayer compliance. In addition, there are several differences with previous research. Among them are the variables used and the research site location.